2010
DOI: 10.1142/s0217751x1004841x
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Non-Fritzsch-Like Texture Specific Quark Mass Matrices

Abstract: A detailed investigation of all possible textures of Fritzsch-like and non-Fritzsch like, 144 for texture 6 zero and 432 for texture 5 zero mass matrices, have been carried out to ascertain their compatibility with the existing quark mixing data. It seems that all the texture 6 zero possibilities are completely ruled out whereas in the case of texture 5 zero mass matrices the only viable possibility looks to be that of Fritzsch-like.Texture specific mass matrices are known to provide satisfactory explanation o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 51 publications
0
26
0
Order By: Relevance
“…In the present work, we have given an overview of all possible cases of Fritzsch-like as well as non Fritzsch-like texture 6 and 5 zero fermion mass matrices, for details see [27,31]. Further, for the case of texture 4 zero Fritzsch-like quark mass matrices, the issue of the hierarchy of the elements of the mass matrices and the role of their phases have been discussed, details can be found in [14,22].…”
Section: Discussionmentioning
confidence: 99%
“…In the present work, we have given an overview of all possible cases of Fritzsch-like as well as non Fritzsch-like texture 6 and 5 zero fermion mass matrices, for details see [27,31]. Further, for the case of texture 4 zero Fritzsch-like quark mass matrices, the issue of the hierarchy of the elements of the mass matrices and the role of their phases have been discussed, details can be found in [14,22].…”
Section: Discussionmentioning
confidence: 99%
“…Four and six texture zeros imply one and three physical relationships respectively, and allow us to write one or the three mixing angles as functions of the six quarks masses and the CP violation phase. But six texture zeros are already ruled out by analytic and numerical considerations [18,19]. 5.…”
Section: Discussionmentioning
confidence: 99%
“…As it has been shown in several places, the parallel and non-parallel six texture zeros does not work properly and it has been ruled out by analytic [18] and numeric [19] studies (only a charm quark mass half of its measured value can rescue this "anzätze").…”
Section: Five Texture Zerosmentioning
confidence: 99%
“…The Fritzsch ansatz totally involves eight independent parameters, and thus it can predict two relations among six quark masses and four flavor mixing parameters. However, it has been shown that this simple ansatz is in conflict with current experimental data [6].…”
Section: Introductionmentioning
confidence: 88%